CIT562: Instructional communication technology / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2016)
This applications course provides both introductory information and application of skills and techniques necessary in the design and development, and evaluation of sound instructional products. These skills are particularly pertinent for efficient and cost effective development of effective solutions to novel instructional problems. This course provides a systematic approach to designing and developing strategies in generating effective instructional communication package. The syllabus of this course guides students to the procedures of implementing a systematic design and development, which involves the process of analyzing, planning, designing, developing and implementation of instructional communication for use in various settings, be it in training management or communication planning.